Battery diaphragm, preparation method thereof and lithium ion battery

By introducing a modified aluminum silicate fiber reinforced coating and ceramic layer into the lithium-ion battery separator, the problem of insufficient mechanical properties and thermal stability of traditional separators under high temperature conditions is solved, and the safety and reliability of the battery are significantly improved.

CN119812676AActive Publication Date: 2025-04-11ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411833331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-11
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators lack mechanical properties and thermal stability under high temperature conditions, which can easily lead to thermal runaway and safety problems of the battery.

Method used

The battery separator design is adopted, including a separator base layer, a ceramic layer and a reinforced coating. The ceramic layer is arranged on at least one side surface of the separator base layer. The reinforced coating consists of modified aluminum silicate fibers and bonded substrates. The modified aluminum silicate fibers are surface modified by silane coupling agent and are uniformly dispersed in the bonded substrate.

Benefits of technology

It significantly improves the mechanical strength, durability and thermal stability of the diaphragm, reduces the risks of mechanical damage and heat shrinkage, and improves the safety and reliability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186077550000121
    Figure BDA0005186077550000121
  • Figure BDA0005186077550000131
    Figure BDA0005186077550000131
Patent Text Reader

Abstract

The invention discloses a battery diaphragm and a preparation method thereof and a lithium ion battery, the battery diaphragm comprises a diaphragm base layer, a ceramic layer arranged on at least one side surface of the diaphragm base layer, and a reinforced coating layer arranged on the surface of the ceramic layer, the reinforced coating layer comprises a bonding matrix and modified aluminum silicate fibers dispersed in the bonding matrix, the modified aluminum silicate fibers are aluminum silicate fibers subjected to surface modification by a silane coupling agent. According to the battery diaphragm, the aluminum silicate fiber subjected to surface modification by the silane coupling agent is used as a reinforcing phase and is dispersed in the bonding matrix, so that the interface bonding force of the aluminum silicate fiber and the bonding matrix can be improved, stress concentration can be effectively dispersed, and the mechanical property, durability and thermal stability of the battery diaphragm are improved; the heat resistance and the safety performance of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a battery separator and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in electronic products, energy storage devices, electric vehicles and other fields. As their applications continue to expand, the safety of lithium batteries has become an important issue. As an important component of the battery, the diaphragm is mainly used to prevent the positive and negative electrodes from directly contacting and short-circuiting. However, traditional diaphragms usually have insufficient mechanical properties and thermal stability, and are prone to failure under high temperature conditions, leading to thermal runaway and safety problems of the battery. Therefore, it is necessary to find a way to enhance the thermal stability and mechanical properties of the battery to ensure the safety of the battery in a high temperature environment. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a battery separator and a preparation method thereof and a lithium ion battery.

[0004] In a first aspect of the present invention, a battery separator is provided, comprising:

[0005] Diaphragm base layer;

[0006] A ceramic layer is provided on at least one side surface of the diaphragm substrate;

[0007] The reinforcing coating is arranged on the surface of the ceramic layer away from the diaphragm base layer; the reinforcing coating comprises a bonding matrix and modified aluminum silicate fibers dispersed in the bonding matrix; the modified aluminum silicate fibers are aluminum silicate fibers surface-modified by a silane coupling agent.

[0008] The battery separator according to the embodiment of the present invention has at least the following beneficial effects: the battery separator uses aluminum silicate fibers surface-modified by a silane coupling agent as a reinforcing phase, and the modified aluminum silicate fibers are uniformly dispersed in a bonding matrix to form a reinforcing coating on the surface of the separator base layer. Among them, aluminum silicate fiber has high strength and high modulus. Introducing it into the coating can significantly improve the strength and toughness of the coating; specifically, aluminum silicate fiber surface-modified by a silane coupling agent is used, and the modified aluminum silicate fiber can react with the bonding matrix to form a strong interface bond, further improving the mechanical strength and durability of the battery separator and reducing the risk of mechanical damage; and the presence of modified aluminum silicate fiber in the coating can effectively disperse stress, reduce stress concentration, avoid material peeling and rupture at the interface, and improve the overall tensile, puncture and compression resistance of the separator; in addition, aluminum silicate fiber has excellent thermal stability and a high melting point. When the coating is subjected to high temperature, the aluminum silicate fiber can maintain its structural integrity and prevent the coating from undergoing significant thermal shrinkage, and the fiber skeleton effect can also provide additional thermal stability for the coating, ensuring the dimensional stability of the coating at high temperatures, reducing the thermal shrinkage rate of the separator, reducing the possibility of melting and deformation of the separator, and improving the high temperature resistance of the battery separator. The battery separator can be further applied to lithium-ion batteries, which can improve the safety of lithium-ion batteries, especially under high temperature or overcharge conditions, and can effectively prevent the separator from shrinking or being damaged, thereby preventing internal short circuits in the battery.

[0009] Specifically, when traditional lithium-ion batteries are working or overcharged in high-temperature environments, the diaphragm material may shrink due to thermal effects, causing the pore structure to collapse or the pore size to change, thereby affecting ion transmission and battery performance, and may even cause internal short circuits in the battery, posing safety risks. The above uses aluminum silicate fibers with high melting points and excellent thermal stability, specifically aluminum silicate fibers surface-modified with silane coupling agents as reinforcing phases, and evenly disperses them in the bonding matrix to form a reinforcing coating on the surface of the diaphragm base layer, which can reduce this shrinkage phenomenon. The modified aluminum silicate fibers are dispersed in the coating as a skeleton structure, which can maintain the integrity of the coating structure at high temperatures, prevent dimensional changes in high temperature environments, and improve the safety and reliability of the battery.

[0010] In some embodiments of the present invention, the battery separator has a needle puncture strength of 300 to 500 gf; an ionic conductivity of ≥6.0 mS / cm; and a thermal shrinkage of <3% at 130°C.

[0011] In some embodiments of the present invention, the thickness of the reinforcement coating is 1 μm to 4 μm. For example, the thickness of the reinforcement coating can be controlled to be 1 μm, 1.5 μm, 2 μm, 3 μm, 3.5 μm, 4 μm, etc.

[0012] In some embodiments of the present invention, the thickness ratio of the diaphragm base layer, the ceramic layer and the reinforcement coating layer is 6-8:0.5-1.5:0.5-1.5.

[0013] In some embodiments of the present invention, the mass of the modified aluminum silicate fiber accounts for 5% to 9% of the mass of the bonding matrix. Further, the mass of the modified aluminum silicate fiber accounts for 5% to 8%, 6% to 8% or 7% to 9% of the mass of the bonding matrix.

[0014] In some embodiments of the present invention, the silane coupling agent contains at least one of an amino group, a hydroxyl group, and an epoxy group; or, the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH550), γ-methacryloxypropyltrimethoxysilane (KH570), γ-chloropropyltrichlorosilane (CPTMS), γ-glycidyloxypropyltrimethoxysilane (KH560), N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (DL602), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), γ-mercaptopropyltrimethoxysilane (KH590), aminopropyltriethoxysilane (APTES), and glycidyltriethoxysilane (GPTMS). Specifically, one of them can be used alone, or two or more of them can be used in combination. For example, the silane coupling agent may be a combination of γ-aminopropyltriethoxysilane (KH550) and γ-methacryloxypropyltrimethoxysilane (KH570), and the mass ratio of KH550 to KH570 may be controlled to be 1:1 to 3:1.

[0015] The surface of aluminum silicate fiber mainly contains silicon oxygen (Si-O) and hydroxyl (-OH) groups. Silane coupling agent can react and bond with these groups. The hydroxyl groups on aluminum silicate fiber can react with the epoxy groups of the coupling agent, so that the coupling agent is completely attached around the fiber. The coupling agent itself has many polar groups, so as to achieve surface modification of aluminum silicate fiber. The above surface modification of aluminum silicate fiber by using silane coupling agent can generate silicon oxygen bonds on the fiber surface, and introduce functional functional groups (such as hydroxyl, amino, epoxy, etc.). These polar or reactive groups can chemically bond with the binder or form a strong interface effect, thereby enhancing the bonding force between the fiber and the binder.

[0016] In some embodiments of the present invention, the material of the bonding matrix is ​​any one of organic coating materials such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), etc. The aluminum silicate fiber surface-modified by a silane coupling agent is dispersed in the bonding matrix, and the surface of the modified aluminum silicate fiber has amino, hydroxyl or other polar groups, which can react with polar molecules in the bonding matrix to form a strong interface bond, thereby improving the mechanical strength of the battery separator.

[0017] In some embodiments of the present invention, the mass ratio of the silane coupling agent to the aluminum silicate fiber is 1:1 to 3. For example, the mass ratio of the silane coupling agent to the aluminum silicate fiber may be 1:1, 1:1.5, 1:2 or 1:3.

[0018] In some embodiments of the present invention, the fiber diameter of the modified aluminum silicate fiber is 500-1500 nm, and the specific surface area is 10-20 m 2 / g. Among them, if the diameter of the modified aluminum silicate fiber is less than 500nm, it will lead to increased difficulty in preparation and increased costs, and the fibers may be excessively accumulated in the coating, affecting the pore structure; if the fiber diameter exceeds 1500nm, the specific surface area decreases, the fiber reinforcement effect weakens, and the uniformity and bonding force of the coating performance are affected. In addition, the surface contact area of ​​the fiber with too small specific surface area (corresponding to a larger diameter) is insufficient, and the interfacial bonding force between the bonding matrix is ​​weakened, affecting the mechanical properties and durability of the coating; and the specific surface area of ​​the fiber is small, which means that the number of fibers per unit mass is small, and a sufficiently dense network structure cannot be formed, which will weaken the enhancement effect on the overall strength of the coating. Thus, the fiber diameter and specific surface area of ​​the modified aluminum silicate fiber are controlled within the above range, which can ensure the strength, uniformity and durability of the enhanced coating, while reducing the difficulty and cost of preparation.

[0019] A ceramic layer is disposed on at least one side of the diaphragm base layer, and the material of the ceramic layer includes an inorganic ceramic material. The high temperature resistance of the battery diaphragm can be improved by disposing the ceramic layer. Firstly, the inorganic ceramic material in the ceramic layer is distributed on the diaphragm base layer to construct a rigid skeleton. With its excellent thermal stability, it can effectively prevent the diaphragm from shrinking and melting under thermal runaway conditions, thereby improving the thermal stability of the battery diaphragm; secondly, the thermal conductivity of the inorganic ceramic material in the ceramic layer can further prevent certain thermal runaway points in the battery from expanding to form overall thermal runaway, thereby improving the safety of the battery.

[0020] In some embodiments of the present invention, the inorganic ceramic material is selected from one or more of Al2O3, SiO2, TiO2, Al(OH)3, MgO, Mg(OH)2, BrSO4, ZrO2, montmorillonite, and boehmite.

[0021] In some embodiments of the present invention, the inorganic ceramic material in the ceramic layer is selected from amphoteric oxides, that is, oxides that are alkaline when exposed to strong acids and acidic when exposed to strong bases. For example, the inorganic ceramic material can be at least one of amphiphilic oxides such as Al2O3, TiO2, and ZrO2. The inorganic ceramic material is an amphoteric oxide, and the inorganic ceramic material in the battery separator can partially absorb impurities such as HF generated in the electrolyte due to the presence of trace water, thereby increasing the service life of the battery.

[0022] In some embodiments of the present invention, the material of the ceramic layer further includes a binder, which may be any one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), and polymethyl methacrylate (PMMA).

[0023] Furthermore, the ceramic layer includes a bonding matrix and an inorganic ceramic material dispersed in the bonding matrix, wherein the bonding matrix is ​​constructed by a binder, and the bonding matrix material in the ceramic layer can be the same as or different from the bonding matrix material in the reinforcement coating.

[0024] In some embodiments of the present invention, the material of the diaphragm base layer is selected from at least one of polypropylene and polyethylene; and / or the diaphragm base layer is a porous diaphragm base layer.

[0025] In a second aspect of the present invention, a method for preparing any of the above-mentioned battery separators is provided, comprising the following steps:

[0026] A ceramic layer is disposed on at least one side surface of the diaphragm substrate;

[0027] The aluminum silicate fiber is placed in a silane coupling agent solution for surface modification to obtain modified aluminum silicate fiber;

[0028] The modified aluminum silicate fiber is mixed with a binder and a solvent to prepare a coating slurry;

[0029] The coating slurry is coated on the surface of the ceramic layer away from the separator base layer, and cured to obtain a battery separator.

[0030] The above preparation method first uses a silane coupling agent to modify the surface of aluminum silicate fiber, so that its surface has functional groups (generally polar groups, such as hydroxyl or amino groups, etc.) for better binding of the binder. Specifically, the chemical interaction between the polar groups on the modified aluminum silicate fiber and the binder is enhanced, thereby improving the mechanical properties of the formed coating; and the surface-modified aluminum silicate fiber has better dispersibility, which can reduce aggregation and improve the uniformity and performance uniformity of the coating.

[0031] In some embodiments of the present invention, a ceramic layer is provided on at least one side of the membrane substrate, comprising: preparing a ceramic slurry by mixing raw materials including an inorganic ceramic material and a binder with a solvent; and then applying the ceramic slurry to at least one side of the membrane substrate, and drying to obtain the ceramic layer. The solvent may be N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), etc.

[0032] In some embodiments of the present invention, before the aluminum silicate fiber is subjected to surface modification treatment, the process further includes: using raw materials including an aluminum source, a silicon source and a grain inhibitor to prepare the aluminum silicate fiber by an electrostatic spinning process. Specifically, the process includes: mixing the aluminum source and the silicon source with an organic solvent, stirring until the solution is clear, and drying to obtain a dry gel; then mixing the dry gel with a solvent, adding a spinning aid, and mixing to obtain a precursor solution; electrostatically spinning the precursor solution to obtain spinning fibers, and sequentially drying and heat treating to obtain the aluminum silicate fiber.

[0033] Among them, the aluminum source can be anhydrous aluminum chloride, aluminum isopropoxide, aluminum nitrate nonahydrate, etc.; preferably anhydrous aluminum chloride. Aluminum isopropoxide, as an organic aluminum source, can be hydrolyzed under certain conditions to generate aluminum oxide; aluminum nitrate nonahydrate can be hydrolyzed and provide aluminum ions, but it needs to be dehydrated.

[0034] Tetraethyl orthosilicate can be used as the silicon source and grain inhibitor. While tetraethyl orthosilicate provides the silicon source, it can also play a grain inhibitory role in the fiber forming process, helping to control the generated silicon oxide structure and prevent excessive crystallization from increasing fiber brittleness.

[0035] The organic solvent used for mixing with the aluminum source and the silicon source can be one or more organic solvents such as ethanol, methanol, isopropanol, isopropyl ether, anhydrous methane, etc. For example, a mixture of isopropyl ether and anhydrous methane can be used.

[0036] The solvent used for mixing with the dry gel can be an alcohol solvent, specifically a low-grade alcohol solvent such as methanol, anhydrous ethanol, propanol, and isopropanol. The uniformity of the precursor solution is adjusted by the solvent to ensure the uniformity of fiber formation.

[0037] The spinning aid can be selected from one or more polymer spinning aids selected from polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and polyacrylonitrile (PAN). The addition of the spinning aid can increase the viscosity of the precursor solution, which helps to form uniform and continuous fibers during spinning. In addition, the spinning aid can be mixed with a solvent to form a spinning aid solution for addition. The solvent is used to help the spinning aid dissolve, which helps to evenly mix the spinning aid in the precursor solution and adjust the viscosity of the precursor solution to obtain a precursor solution with suitable spinning fluidity. Among them, the solvent can be N, N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), etc., and the specific effect on the solution viscosity and spinning effect needs to be investigated.

[0038] During the preparation process of aluminum silicate fiber, the drying temperature can be controlled at 60℃~100℃ or 70℃~100℃, such as the drying temperature can be controlled at 60℃, 65℃, 70℃, 80℃, 85℃, 90℃, 100℃, etc.; the heat treatment temperature can be controlled at 700℃~900℃, for example, it can be 700℃, 720℃, 750℃, 760℃, 800℃, 850℃, 900℃, etc.

[0039] In some embodiments of the present invention, the silane coupling agent solution can be prepared by mixing the silane coupling agent with a solvent, wherein the mass ratio of the silane coupling agent to the solvent can be controlled to be 1:10 to 1:20, such as 1:12, 1:15, 1:18, etc.; the solvent can be anhydrous ethanol or isopropanol.

[0040] In some embodiments of the present invention, when the aluminum silicate fiber is placed in a silane coupling agent solution, the mass ratio of the silane coupling agent to the aluminum silicate fiber is controlled to be 1:1-4.

[0041] In some embodiments of the present invention, during the preparation of the coating slurry, the mass ratio of the modified aluminum silicate fiber to the binder is controlled to be 5% to 9%.

[0042] In some embodiments of the present invention, the modified aluminum silicate fiber is mixed with a binder and a solvent to prepare a coating slurry, specifically comprising: firstly mixing the binder and the solvent to obtain a binder solution; and then dispersing the modified aluminum silicate fiber in the binder solution to obtain a coating slurry. The solvent may be N-methylpyrrolidone (NMP) or N,N-dimethylacetamide (DMAC), and the mass concentration of the binder solution may be controlled at 10% to 15%.

[0043] In some embodiments of the present invention, the modified aluminum silicate fiber is dispersed in the binder solution, specifically comprising: adding the modified aluminum silicate fiber to the binder solution, and then performing ultrasonic dispersion and mechanical stirring in sequence. If a conventional mechanical stirring dispersion method is used, the modified aluminum silicate fiber may agglomerate, resulting in uneven coating reinforcement effect and even local failure. By adopting a dispersion method combining ultrasonic dispersion and mechanical stirring, it is possible to ensure that the modified aluminum silicate fiber is uniformly dispersed in the binder solution, so that the aluminum silicate fiber in the reinforcement coating is uniformly dispersed in the bonding matrix, thereby enhancing the mechanical properties of the product battery separator.

[0044] In some embodiments of the present invention, after the surface of the ceramic layer is coated with the coating slurry, the curing method adopts thermal curing, and after curing, the binder solution forms a curing matrix, and the modified aluminum silicate fiber is evenly dispersed in the bonding matrix, thereby forming a reinforcing coating on the surface of the diaphragm base to obtain a battery diaphragm. Among them, the temperature of thermal curing can be controlled at 150℃~200℃, 160℃~200℃, 170℃~180℃ or 165℃~185℃. By thermal curing at about 180℃, the crystallinity and mechanical properties of the bonding matrix formed by curing the binder solution can reach a better state, thereby improving the overall performance of the reinforcing coating.

[0045] The third aspect of the present invention provides the aforementioned lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator sandwiched between the positive electrode sheet and the negative electrode sheet, wherein the separator is any of the aforementioned battery separators. DETAILED DESCRIPTION

[0046] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0047] Example 1

[0048] This embodiment proposes a battery diaphragm, which includes a diaphragm base, a ceramic layer and a reinforcing coating, wherein the ceramic layer is arranged on both sides of the diaphragm base, and the reinforcing coating is arranged on the surface of the ceramic layer away from the diaphragm base, and the reinforcing coating includes a bonding matrix and modified aluminum silicate fibers dispersed in the bonding matrix, and the modified aluminum silicate fibers are aluminum silicate fibers surface-modified by a silane coupling agent. Among them, the silane coupling agent adopts a mixture of γ-aminopropyl triethoxysilane (KH550) and γ-methacryloxypropyl trimethoxysilane (KH570) with a mass ratio of 1:2, and the diaphragm base adopts a polyethylene film with a thickness of 7μm; the thickness of the reinforcing coating is 1μm, and the mass of the modified aluminum silicate fibers in the reinforcing coating accounts for 5% of the mass of the bonding matrix, and the material of the bonding matrix is ​​polyvinylidene fluoride (PVDF).

[0049] The preparation method of the battery separator is as follows:

[0050] S1. Preparation of aluminum silicate fiber. Specifically, 0.4 g of anhydrous aluminum chloride was weighed and put into a 100 ml beaker, and 0.22 ml of tetraethyl orthosilicate was measured with a pipette and evenly added; 3.5 ml of isopropyl ether and 15 ml of anhydrous dichloromethane were slowly added thereto, and magnetic stirring was performed at a constant temperature until the solution was clear, and the obtained solution was dried in a drying oven at 100 ° C to obtain a dry gel, and 10.5 ml of anhydrous ethanol was measured and poured into the prepared dry gel, and then 0.5 g of polyvinyl pyrrolidone (PVP, molecular weight 1.3 million) and 1.5 ml of N, N-dimethylformamide is stirred evenly to obtain a precursor solution; the precursor solution is subjected to electrostatic spinning, specifically using a 0.8mm needle, setting the voltage to 23KV, the flow rate to 2ml / h, and the distance between the needle and the receiving plate to 17.6cm. After the spinning is completed, the collected spun fibers are placed in an 80℃ drying oven for 16h, and the dried fibers are heat treated in an 800℃ box-type resistance furnace for 1h to obtain flexible aluminum silicate fibers with a fiber diameter of about 600nm and a specific surface area of ​​about 15㎡ / g.

[0051] S2, dissolving the silane coupling agent in anhydrous ethanol at a mass ratio of 1:10 to the solvent anhydrous ethanol to obtain a silane coupling agent solution; placing the aluminum silicate fiber obtained in step S1 in the silane coupling agent solution at a mass ratio of 1:1 to the aluminum silicate fiber, reacting at 60°C for 2 hours, and then drying to obtain modified aluminum silicate fibers with active groups on the surface; dissolving polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) to prepare a PVDF solution with a concentration of 10%, and then adding the modified aluminum silicate fiber obtained in step S2 to the PVDF solution at an amount of 5% of the mass of the modified aluminum silicate fiber, first performing ultrasonic dispersion to promote uniform dispersion of the modified aluminum silicate fiber in the solution, and then performing mechanical stirring for 2.5 hours to uniformly disperse the modified aluminum silicate fiber in the mixed solution to obtain a coating slurry.

[0052] S3. A polyethylene film with a thickness of 7 μm is used as the base layer of the diaphragm. The inorganic ceramic material adopts a combination of aluminum oxide (Al2O3) and titanium dioxide (TiO2) in a mass ratio of 7:3. The inorganic ceramic material, a binder and a solvent DMF are mixed in a mass ratio of 9:1:13.5 to form a ceramic slurry. The ceramic slurry is coated on the surfaces of both sides of the diaphragm base to form a ceramic layer with a thickness of 1 μm. The coating slurry obtained in step S3 is then coated on the surface of the ceramic layer. After drying, a reinforcing coating with a thickness of 1 μm is obtained. The total thickness of the reinforcing coating on the battery diaphragm is 2 μm.

[0053] Example 2

[0054] This embodiment proposes a battery separator. The difference between this embodiment and Example 1 is that in this embodiment, modified aluminum silicate fiber is added to the PVDF solution according to the addition amount of modified aluminum silicate fiber accounting for 3% of the PVDF mass. The other structures and preparation operations are the same as those in Example 1.

[0055] Example 3

[0056] This embodiment proposes a battery separator. The difference between this embodiment and Example 1 is that in this embodiment, the modified aluminum silicate fiber is added to the PVDF solution according to the addition amount of the modified aluminum silicate fiber accounting for 8% of the mass of PVDF. The other structures and preparation operations are the same as those in Example 1.

[0057] Example 4

[0058] This embodiment proposes a battery separator. The difference between this embodiment and Example 1 is that in this embodiment, the modified aluminum silicate fiber is added to the PVDF solution according to the addition amount of the modified aluminum silicate fiber accounting for 10% of the PVDF mass. The other structures and preparation operations are the same as those in Example 1.

[0059] Example 5

[0060] This embodiment proposes a battery separator. The difference between this embodiment and Example 1 is that the mass ratio of silane coupling agent to aluminum silicate fiber is 1:0.5, and the other structures and preparation operations are the same as those in Example 1.

[0061] Example 6

[0062] This embodiment proposes a battery separator. The difference between this embodiment and Example 1 is that the mass ratio of silane coupling agent to aluminum silicate fiber is 1:3, and other structures and preparation operations are the same as those in Example 1.

[0063] Example 7

[0064] This embodiment proposes a battery separator. The difference between this embodiment and Example 1 is that the mass ratio of silane coupling agent to aluminum silicate fiber is 1:4, and other structures and preparation operations are the same as those in Example 1.

[0065] Example 8

[0066] This embodiment proposes a battery separator. The difference between this embodiment and embodiment 1 is that a polyethylene film with a thickness of 7 μm is used as the separator base layer, and a ceramic layer with a thickness of 1 μm is firstly arranged on the surface of both sides of the separator base layer; and then the coating slurry obtained in step S3 is coated on the surface of the ceramic layer on only one side, and a reinforced coating with a thickness of 1 μm is obtained after drying.

[0067] Example 9

[0068] This embodiment proposes a battery separator. The difference between this embodiment and embodiment 1 is that a polyethylene film with a thickness of 7 μm is used as the separator base layer, and a ceramic layer with a thickness of 1 μm is firstly arranged on the surface of both sides of the separator base layer; and then the coating slurry obtained in step S3 is coated on the surface of the ceramic layer on only one side, and a reinforced coating with a thickness of 2 μm is obtained after drying.

[0069] Example 10

[0070] This embodiment proposes a battery separator. The difference between this embodiment and embodiment 1 is that a polyethylene film with a thickness of 7 μm is used as the separator base layer, and a ceramic layer with a thickness of 1 μm is first arranged on the two side surfaces of the separator base layer; then the coating slurry obtained in step S3 is coated on the surface of the ceramic layer, and a reinforced coating with a thickness of 2 μm is obtained after drying. The total thickness of the reinforced coating on the battery separator is 4 μm.

[0071] Comparative Example 1

[0072] This comparative example proposes a battery separator. The difference between this comparative example and Example 1 is that this comparative example uses a PVDF coating with a thickness of 2 μm to replace the reinforcement coating in Example 1, that is, no modified aluminum silicate fiber is added to the PVDF coating in this comparative example, and the other structures are the same as those in Example 1. The preparation method of the battery separator is as follows:

[0073] A polyethylene film with a thickness of 7 μm is used as the base layer of the diaphragm, and a ceramic layer with a thickness of 1 μm is firstly arranged on the two side surfaces of the base layer of the diaphragm; PVDF is dissolved in solvent water to obtain a PVDF solution, and the PVDF solution is coated on the surface of the ceramic layer, and a PVDF coating with a thickness of 1 μm is prepared after drying.

[0074] Comparative Example 2

[0075] This comparative example proposes a battery separator. The difference between this comparative example and Example 1 is that the operation of step S2 in the preparation process of the battery separator in this comparative example is different from that in Example 1. In step S2 of this comparative example, the silane coupling agent, aluminum silicate fiber and PVDF are directly mixed in solvent water to prepare a coating slurry, and other operations are similar to those in Example 1. The specific preparation method is as follows:

[0076] S1, the operation is the same as step S1 in Example 1;

[0077] S2, dissolving the silane coupling agent in anhydrous ethanol according to the mass ratio of silane coupling agent to solvent anhydrous ethanol of 1:10 to obtain a silane coupling agent solution; dissolving polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) to prepare a PVDF solution with a concentration of 10%; placing the aluminum silicate fiber obtained in step S1, the silane coupling agent solution, and the PVDF solution in a round-bottom flask according to the mass ratio of aluminum silicate fiber to silane coupling agent and PVDF of 1:1:20, and performing ultrasonic dispersion and mechanical stirring in sequence to obtain a coating slurry;

[0078] S3. Similar to step S3 in Example 1, a polyethylene film with a thickness of 7 μm is used as the diaphragm base layer, and a ceramic layer with a thickness of 1 μm is first set on the two side surfaces of the diaphragm base layer; then the coating slurry obtained in step S2 is coated on the surface of the ceramic layer, and a reinforced coating with a thickness of 1 μm is obtained after drying.

[0079] Comparative Example 3

[0080] This comparative example proposes a battery separator. The difference between this comparative example and Example 1 is that the operation of step S2 in the preparation process of the battery separator in this comparative example is different from that in Example 1. In step S2 of this comparative example, silane coupling agent is first mixed with PVDF for modification, and then aluminum silicate fiber is added to mix and prepare a coating slurry. Other operations are similar to those in Example 1. The specific preparation method is as follows:

[0081] S1, the operation is the same as step S1 in Example 1;

[0082] S2. According to the mass ratio of silane coupling agent to solvent anhydrous ethanol being 1:10, the silane coupling agent is dissolved in anhydrous ethanol to obtain a silane coupling agent solution; polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP) to prepare a PVDF solution with a concentration of 10%; according to the mass ratio of silane coupling agent to PVDF being 1:20, the silane coupling agent solution and the PVDF solution are placed in a round-bottom flask, and ultrasonic dispersion and mechanical stirring are performed in sequence to obtain a mixed solution; then the mixed solution is evenly coated on the aluminum silicate fiber, and the above-mentioned mixed solution is gently pushed with a glass rod to make the aluminum silicate fiber fully immersed in the mixed solution to obtain a coating slurry.

[0083] S3. Similar to step S3 in Example 1, a polyethylene film with a thickness of 7 μm is used as the diaphragm base layer, and a ceramic layer with a thickness of 1 μm is first set on the two side surfaces of the diaphragm base layer; then the coating slurry obtained in step S2 is coated on the surface of the ceramic layer, and a reinforced coating with a thickness of 1 μm is obtained after drying.

[0084] Comparative Example 4

[0085] This comparative example proposes a battery separator. The difference between this comparative example and Example 1 is that in the preparation process of the battery separator in this comparative example, PVDF modified by a silane coupling agent is used to prepare the coating slurry, and aluminum silicate fiber is not added. The specific preparation method is as follows:

[0086] S1. According to the mass ratio of silane coupling agent to solvent anhydrous ethanol of 1:10, the silane coupling agent is dissolved in anhydrous ethanol to obtain a silane coupling agent solution; polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP) to prepare a PVDF solution with a concentration of 10%; according to the mass ratio of silane coupling agent to PVDF of 1:20, the silane coupling agent solution and the PVDF solution are placed in a round-bottom flask, and ultrasonic dispersion and mechanical stirring are performed in turn to obtain a silane coupling agent modified PVDF coating slurry.

[0087] S2. Similar to step S3 in Example 1, a polyethylene film with a thickness of 7 μm is used as the diaphragm base layer, and a ceramic layer with a thickness of 1 μm is first set on the surface of both sides of the diaphragm base layer; then the coating slurry obtained in step S1 is coated on the surface of the ceramic layer, and a reinforced coating with a thickness of 1 μm is obtained after drying.

[0088] Comparative Example 5

[0089] This comparative example proposes a battery separator. The difference between this comparative example and Example 1 is that in the preparation process of the battery separator in this comparative example, aluminum silicate fiber is directly mixed with PVDF to prepare a coating slurry, and the aluminum silicate fiber is not modified by a silane coupling agent. The specific preparation method is as follows:

[0090] S1, the operation is the same as step S1 in Example 1;

[0091] S2. Dissolve polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) to prepare a 10% PVDF solution; according to the mass ratio of aluminum silicate fiber to PVDF of 1:20, place unmodified aluminum silicate fiber and PVDF solution in a round-bottom flask, first perform ultrasonic dispersion to promote the uniform dispersion of aluminum silicate fiber in the solution, and then perform mechanical stirring for 2.5 hours to obtain a PVDF coating slurry containing unmodified aluminum silicate fiber.

[0092] S3. Similar to step S3 in Example 1, a polyethylene film with a thickness of 7 μm is used as the diaphragm base layer, and a ceramic layer with a thickness of 1 μm is first set on the two side surfaces of the diaphragm base layer; then the coating slurry obtained in step S1 is coated on the surface of the ceramic layer, and a reinforced coating with a thickness of 1 μm is obtained after drying.

[0093] Embodiment 11

[0094] This embodiment provides a lithium ion battery, and the preparation method thereof includes:

[0095] (1) Preparation of positive electrode

[0096] The positive electrode material lithium cobalt oxide, mixed conductive agent (cobalt trioxide, nickel trioxide and manganese oxide in a mass ratio of 1:1:1), and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system in a mass ratio of 98:1.0:1.0, coated on Al foil, and dried, rolled, and slit to obtain a positive electrode sheet.

[0097] (2) Preparation of negative electrode

[0098] Graphite or silicon-carbon negative electrode material, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 97.8:1.1:1.1, and then coated on Cu foil. After drying, rolling, and slitting, a negative electrode sheet is obtained.

[0099] (3) Preparation of electrolyte

[0100] A solution prepared by mixing lithium salt LiPF6 and a non-aqueous organic solvent in a mass ratio of 8:92 is used as the electrolyte of a lithium battery, wherein the non-aqueous organic solvent is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) in a mass ratio of 25:25:15:31:4.

[0101] (4) Assembly of lithium-ion batteries

[0102] The battery separator prepared in Example 1 is used as the separator of this embodiment, and the positive electrode sheet and separator prepared in step S1 and the negative electrode sheet prepared in step S2 are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, and the electrolyte prepared in step S3 is injected and packaged to obtain a lithium-ion battery.

[0103] Examples 12 to 20

[0104] Examples 12 to 20 respectively prepare a lithium ion battery. The difference between Examples 12 to 20 and Example 11 is that the battery separators of the lithium ion batteries in Examples 12 to 20 respectively adopt the battery separators of Examples 2 to 10, and other operations are the same as Example 11.

[0105] Comparative Examples 6 to 10

[0106] Comparative Examples 6 to 10 respectively prepared a lithium ion battery. The difference between Comparative Examples 6 to 10 and Example 11 is that the battery separators of the lithium ion batteries in Comparative Examples 6 to 10 respectively adopted the battery separators of Comparative Examples 1 to 5, and the other operations were the same as Example 11.

[0107] Performance Testing

[0108] The battery separators of Examples 1 to 10 and the battery separators of Comparative Examples 1 to 5 were tested for heat shrinkage, needle puncture strength and ionic conductivity.

[0109] The heat shrinkage test condition is to maintain the temperature at 130°C for 0.5h.

[0110] The test method of needle puncture strength is as follows: flatten the battery separator in the fixture and clamp it, puncture it at a rate of (100±10)mm / min, take out the sample after completion, read the maximum load of the steel needle penetrating the test piece, and the instrument automatically calculates the puncture strength. Among them, the number of test pieces is more than 5, and the average value is taken.

[0111] The test method for ionic conductivity is: determined according to the recorded method in GBT36363-2018 "Polyolefin separators for lithium-ion batteries".

[0112] The performance of the battery separators of each embodiment and comparative example was tested according to the above method, and the results are shown in Table 1, wherein the thermal shrinkage rate in the MD direction represents the thermal shrinkage rate in the length direction of the battery separator; the thermal shrinkage rate in the TD direction represents the thermal shrinkage rate in the width direction of the battery separator.

[0113] In addition, the thermal stability of the lithium ion batteries prepared in Examples 11 to 20 and the lithium ion batteries of Comparative Examples 6 to 10 were tested respectively, and the specific testing methods are as follows:

[0114] Preparation process: Place at room temperature (25℃±3℃) for 5 minutes, then discharge at 0.2C constant current to 3.0V and place for 5 minutes; continue to charge at 2C constant current and constant voltage to 4.25V, with a cut-off rate of 1.5C; finally charge at 1.5C constant current and constant voltage to 4.53V, with a cut-off rate of 0.05C; place for 120 minutes and then use for testing.

[0115] Test process: Put the prepared lithium-ion batteries into different ovens, raise the temperature to the set temperature (126°C, 127°C, 128°C, 129, 130°C, 132°C, 133°C, 134°C) at a rate of 5±2°C / min, and keep it for 60 minutes before stopping. Comparative Examples 6-10 and Examples 11-20 each put 5 lithium-ion batteries in ovens set at different temperatures. During the test, it is necessary to monitor the surface temperature, ambient temperature and voltage of the lithium-ion battery; if the lithium-ion battery does not catch fire or explode, it is qualified. Table 1 shows the highest temperature that the tested battery can withstand.

[0116] Table 1 Performance test results data

[0117]

[0118]

[0119] From Table 1 above, comparing Example 1 with Comparative Example 1, and Example 11 with Comparative Example 6, it can be seen that coating the surface of the diaphragm base with a silane coupling agent-modified aluminum silicate fiber-PVDF composite coating can improve the needle puncture strength and ion conductivity of the battery diaphragm, reduce the thermal shrinkage of the battery diaphragm, and improve the safety performance of the lithium-ion battery. This is because aluminum silicate fiber as a reinforcing phase can improve the mechanical strength of the PVDF matrix, so the coated battery diaphragm exhibits higher strength when punctured or compressed, and significantly improves the thermal stability of the battery diaphragm, reduces shrinkage at high temperatures, and thus can improve the heat resistance and safety performance of the battery.

[0120] Comparing the performance test results of the battery separators of Example 1 and Example 2, it can be seen that the aluminum silicate fiber content is insufficient, resulting in limited improvement in needle puncture strength and thermal shrinkage. Comparing the performance test results of the battery separators of Example 1 and Example 3, it can be seen that when the mass ratio of modified aluminum silicate fiber added to the PVDF solution increases, the needle puncture strength, thermal shrinkage and ionic conductivity of the battery separator reach an optimal balance. Comparing the performance test results of the battery separators of Example 1 and Implementation 4, it can be seen that when the fiber content exceeds a certain proportion (such as 10%), it may cause fiber agglomeration and uneven distribution, reducing the enhancement efficiency. Agglomeration may lead to a decrease in needle puncture strength and ionic conductivity, and limited performance improvement. Therefore, the mass ratio of aluminum silicate fiber to PVDF is recommended to be controlled at 5% to 9%. Within this range, the optimal balance can be achieved between mechanical properties, thermal stability and electrical conductivity.

[0121] Comparing the performance test results of the battery separators of Example 1 and Example 5, it can be seen that the amount of silane coupling agent used is the largest, the modification effect is the best, the needle puncture strength, thermal shrinkage, and ionic conductivity are slightly worse, but the cost is higher. Comparing the performance test results of the battery separators of Example 1, Example 6, and Example 7, it can be seen that when the mass ratio of the silane coupling agent to the aluminum silicate fiber is reduced, the weaker the needle puncture strength of the battery separator, the higher the thermal shrinkage, and the lower the ionic conductivity. This is because the surface modification effect of the aluminum silicate fiber may be weakened, resulting in a decrease in the bonding strength between the fiber and the PVDF matrix. This decrease in bonding strength will have an impact on the performance of the battery separator. If the balance between performance and cost is to be achieved, it is recommended that the mass ratio of silane coupling agent to aluminum silicate fiber is between 1:1 and 1:3, which can achieve a balanced performance between mechanical properties, thermal stability, and ionic conductivity.

[0122] By comparing the performance test results of the battery separators of Examples 1 and 8 to 10, it can be seen that the 1 μm reinforcement coating on both sides of the base film (Example 1) can effectively improve the needle puncture strength and heat shrinkage while maintaining good air permeability and ionic conductivity, showing a better performance balance. In the case of 2 μm coating on both sides (Example 10), although the mechanical strength and thermal stability are optimal, the ionic conductivity decreases due to the thicker coating. In contrast, the single-sided coating of 1 μm (Example 8) has better economy and is suitable for scenarios where cost and process simplification are required, but the mechanical strength and thermal stability are slightly inferior to the double-sided coating design. The single-sided coating of 2 μm (Example 9) can improve the mechanical strength, but due to the uneven stress distribution, the overall performance is not as good as the double-sided coating. Therefore, the coating method of 1 μm on each side achieves a good balance between mechanical properties, thermal stability and ionic conductivity, and is the solution with the best comprehensive performance.

[0123] By comparing the battery separators of Example 1 and Comparative Examples 2 to 5, and the lithium-ion batteries of Example 11 and Comparative Examples 7 to 10, it can be seen that it is advantageous to first surface-modify the aluminum silicate fiber with a silane coupling agent and then mix it with PVDF. This is because in Example 1, the aluminum silicate fiber is first surface-modified with a silane coupling agent and then mixed with PVDF. After the aluminum silicate fiber is surface-modified with a silane coupling agent, the surface has functional functional groups (such as amino or hydroxyl groups, etc.), and the chemical interaction between these functional groups and PVDF is enhanced, so that it can better combine with the PVDF matrix and improve the mechanical properties of the coating; and the surface-modified aluminum silicate fiber is easier to be evenly dispersed in PVDF, reducing aggregation, which can improve the uniformity and performance consistency of the coating and improve the thermal stability of the battery.

[0124] In Comparative Example 2, when silane coupling agent, PVDF and aluminum silicate fiber co-exist, the reaction of silane coupling agent is not sufficient, because they may preferentially react with polar groups in PVDF, reducing the reaction time and opportunity with the surface of aluminum silicate fiber, resulting in unsatisfactory modification effect of the surface of aluminum silicate fiber; and since the surface of aluminum silicate fiber is not completely modified, the bonding force between aluminum silicate fiber and PVDF matrix is ​​insufficient, resulting in decreased mechanical properties and stability of coating; in addition, it will also affect the dispersion of fiber, reduce the uniformity and structural stability of coating, and thus reduce the thermal stability of battery.

[0125] In Comparative Example 3, after the silane coupling agent reacts with PVDF first, the polar group of the silane coupling agent has already combined with PVDF and can no longer effectively react with the hydroxyl groups or oxides on the surface of the aluminum silicate fiber, resulting in insufficient surface modification of the aluminum silicate fiber; since the aluminum silicate fiber has not been effectively modified, its bonding force with PVDF is still low, which will lead to poor stress transfer efficiency at the interface and affect the mechanical properties of the diaphragm.

[0126] Aluminum silicate fiber has excellent thermal stability and can improve the high temperature resistance of composite materials. Compared with the comparative example 4 in which PVDF is modified by silane coupling agent without adding aluminum silicate fiber, the stability of the battery separators in various embodiments in high temperature application scenarios (such as batteries) is better; while the surface of aluminum silicate fiber in comparative example 5 is not modified by silane coupling agent, and the interface bonding force between the aluminum silicate fiber and the PVDF matrix is ​​poor. The surface of aluminum silicate fiber is relatively inert and lacks polar functional groups that interact strongly with the matrix, resulting in the bonding force between aluminum silicate fiber and PVDF matrix mainly relying on physical adsorption and mechanical interlocking.

[0127] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A battery separator, characterized in that: include: Diaphragm base layer; A ceramic layer is provided on at least one side surface of the diaphragm substrate; A reinforcement coating is provided on the surface of the ceramic layer away from the diaphragm base layer; The reinforcement coating comprises a bonding matrix and modified aluminum silicate fibers dispersed in the bonding matrix; The modified aluminum silicate fiber is an aluminum silicate fiber whose surface is modified by a silane coupling agent.

2. The battery separator according to claim 1, characterized in that: The battery separator has a needle puncture strength of 300-500 gf, an ionic conductivity of ≥6.0 mS / cm, and a thermal shrinkage rate of <3% at 130°C.

3. The battery separator according to claim 1, characterized in that: The thickness of the reinforcement coating is 1 μm to 4 μm; and / or the thickness ratio of the diaphragm base layer, the ceramic layer and the reinforcement coating is 6 to 8: 0.5 to 1.5: 0.5 to 1.

5.

4. The battery separator according to claim 1, characterized in that: The mass ratio of the modified aluminum silicate fiber to the bonding matrix is ​​5% to 9%.

5. The battery separator according to claim 1, characterized in that: The modified aluminum silicate fiber has a fiber diameter of 500 to 1500 nm and a specific surface area of ​​10 to 20 m 2 / g.

6. The battery separator according to claim 1, characterized in that: The silane coupling agent contains at least one of amino, hydroxyl and epoxy groups; or, the silane coupling agent is selected from at least one of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-chloropropyl trichlorosilane, γ-glycidyloxypropyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl methyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, aminopropyl triethoxysilane and epoxypropyl triethoxysilane; And / or, the mass ratio of the silane coupling agent to the aluminum silicate fiber is 1:1-3.

7. The battery separator according to any one of claims 1 to 6, characterized in that The material of the diaphragm base layer is selected from at least one of polypropylene and polyethylene; and / or the diaphragm base layer is a porous diaphragm base layer.

8. The method for preparing a battery separator according to any one of claims 1 to 7, characterized in that: The following steps are involved: A ceramic layer is disposed on at least one side surface of the diaphragm substrate; The aluminum silicate fiber is placed in a silane coupling agent solution for surface modification to obtain modified aluminum silicate fiber; The modified aluminum silicate fiber is mixed with a binder and a solvent to prepare a coating slurry; The coating slurry is coated on the surface of the ceramic layer away from the separator base layer, and cured to obtain a battery separator.

9. The method for preparing a battery separator according to claim 8, characterized in that: The modified aluminum silicate fiber is mixed with a binder and a solvent to prepare a coating slurry, specifically comprising: firstly mixing the binder and the solvent to obtain a binder solution; and then dispersing the modified aluminum silicate fiber in the binder solution to obtain a coating slurry.

10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet and a separator sandwiched between the positive electrode sheet and the negative electrode sheet, wherein the separator is the battery separator according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Battery separator, preparation method thereof and battery

    CN109841779A

  • Low-moisture solvent type PVDF (Polyvinylidene Fluoride) coated diaphragm

    CN113594632A

  • Diaphragm and preparation method thereof, secondary battery and electric device

    CN115911748A

  • Heat-resistant lithium ion battery composite diaphragm

    CN220672793U

  • Composite separator, manufacturing method therefor, and secondary battery

    WO2023005291A1

Cited By

  • Diaphragm, preparation method thereof and lithium ion battery

    CN120601069A